Financial Distress Before and During Pandemic Covid-19: Is Islamic Banking in Indonesia Resilience? - Fadhila Meithasari Nurtjahjo; Tita Nursyamsiah; Mohammad Iqbal Irfany (Universitas Muhammadiyah Malang, 2022)
This study aims to predicts financial distress before and during the pandemic and to analyze the influence factors on the financial distress of sharia commercial banks in Indonesia. This study was quantitatif used purposive sampling method with twelve Islamic commercial banks in Indonesia as samples based on these criteria. Data were analyzed and processed by using Microsoft Excel 2016 and SPSS 22 software. The result found that most Islamic banks in Indonesia were in a positive financial condition before and during the pandemic Covid-19. Further, the result also found that NOM had a significant negative effect in all models, OER had a significant positive impact in all models, CAR had a significant negative effect in the first and second models, and GDP had a significant negative impact in the second until fifth models. Meanwhile, size, exchange rate, and inflation do not significantly affect financial distress of Islamic commercial banks in Indonesia before and during the pandemic Covid-19.